2014
DOI: 10.1016/j.aidm.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Liver cirrhosis as a predisposing factor for esophageal candidiasis

Abstract: Summary Background Esophageal candidiasis (EC) often occurs in human immunodeficiency virus (HIV)‐infected patients, but is uncommon in non‐HIV‐infected patients. It is known that malignancy, diabetes mellitus, previous gastric surgery, and medications (antibiotics, proton pump inhibitors, and steroids) are risk factors for esophageal candidiasis in non‐HIV‐infected patients. However, the relationship between liver cirrhosis and esophageal candidiasis was unclear. This study aimed to elucidate the role of live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Early prevention of these second infections is suggested. However, whether esophageal candidiasis affected the outcomes of patients with liver cirrhosis was not reported by Ou et al [1]. Instead, they found no difference in the mortality during hospitalization between patients with and without antifungal treatment, and also found that antifungal treatment did not decrease the mortality in cirrhotic patients with esophageal candidiasis.…”
Section: Conflicts Of Interestmentioning
confidence: 87%
See 4 more Smart Citations
“…Early prevention of these second infections is suggested. However, whether esophageal candidiasis affected the outcomes of patients with liver cirrhosis was not reported by Ou et al [1]. Instead, they found no difference in the mortality during hospitalization between patients with and without antifungal treatment, and also found that antifungal treatment did not decrease the mortality in cirrhotic patients with esophageal candidiasis.…”
Section: Conflicts Of Interestmentioning
confidence: 87%
“…Candida esophagitis is the most common infectious disease of the esophagus and the most common gastrointestinal opportunistic disorder among individuals infected with human immunodeficiency virus (HIV). Ou et al [1] conducted a study using a retrospective chart review of non‐HIV‐infected patients with esophageal candidiasis and particularly aimed to elucidate the role of liver cirrhosis in esophageal candidiasis. I have long thought that retrospective chart reviews are usually poorly done and are subject to all sorts of biases and confounding issues.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 3 more Smart Citations